HUBUNGAN ANTARA PERAWATAN LUKA PERINEUM MASA NIFAS DENGAN LAMANYA PENYEMBUHAN LUKA PERINEUM DI KLINIK KYODDAFA SUNGAI DAREH KABUPATEN DHARMASRAYA TAHUN 2025 - Sari, Evin Noviana; Nensi, Yepni; Khotimah, Siti; Astuti, Sri Andar Puji (Ensiklopedia of Journal, 2025)
Postpartum is a period of recovery for the reproductive organs, lasting approximately 6-8 weeks. During the postpartum period, care is necessary to aid the involution process. Lack of perineal care can delay wound healing and even lead to infection. Based on data from the KyoDafa Clinic in Sungai Dareh, Dharmasraya Regency, in 2025, 23 of 33 postpartum women experienced delayed perineal wound healing. This is due to several factors, including inadequate perineal wound care. This study aims to analyze the relationship between postpartum perineal wound care and the duration of perineal wound healing at the KyoDafa Clinic in Sungai Dareh, Dharmasraya Regency, in 2025. The research method used was correlational analytic. The population in this study was 36 postpartum women with perineal wounds at the KyoDafa Clinic in Sungai Dareh, with a sample size of 33. The sampling technique used was purposive sampling. Based on the Mann–Whitney test, the AsympSig value is smaller than α, which is 0.00, smaller than 0.05, meaning H0 is rejected and H1 is accepted. Thus, it can be said that there is a relationship between perineal wound care and the duration of perineal wound healing in postpartum mothers at the KyoDafa Clinic in Sungai Dareh in 2025. Based on these research results, midwives must establish collaboration by providing knowledge about the importance of perineal wound care in postpartum mothers.Keywords: Perineal Wound Care, Perineal Wound Healing, Postpartum Mothers